login
a(n) = (4*9^n + (-1)^n)/5.
2

%I #16 Sep 08 2022 08:45:10

%S 1,7,65,583,5249,47239,425153,3826375,34437377,309936391,2789427521,

%T 25104847687,225943629185,2033492662663,18301433963969,

%U 164712905675719,1482416151081473,13341745359733255,120075708237599297

%N a(n) = (4*9^n + (-1)^n)/5.

%C Binomial transform of A083301.

%H Vincenzo Librandi, <a href="/A083302/b083302.txt">Table of n, a(n) for n = 0..300</a>

%H <a href="/index/Rec#order_02">Index entries for linear recurrences with constant coefficients</a>, signature (8,9).

%F G.f.: (1-x)/((1-*9x)(1+x)).

%F E.g.f.: (4*exp(9*x) + exp(-x))/5.

%o (Magma) [(4*9^n+(-1)^n)/5: n in [0..25]]; // _Vincenzo Librandi_, Jun 29 2011

%o (PARI) a(n)=4*9^n\/5 \\ _Charles R Greathouse IV_, Jun 29 2011

%K easy,nonn

%O 0,2

%A _Paul Barry_, Apr 24 2003